Effectiveness of Compensatory Rehabilitation on Neuropsychological Functions of Preschool Children with Attention Deficit Hyperactivity Disorder Symptoms - Mahdis Maghsudloo; Vahid Nejati; Jalil Fathabadi (Shiraz University of Medical Sciences, 2018)
Background: Executive functions are impaired in children with attention deficithyperactivity disorder. One method to improve these functions is Compensatory rehabilitation. This study aims to assess the effectiveness of compensatory rehabilitation training on neuropsychological functions in preschool children with attention deficit- hyperactivity disorder (ADHD) symptoms. Methods: This is an experimental study by pretest, posttest and follow-up design with control group. Thirty two (32) children with attention deficithyperactivity disorder symptoms were selected using convenience sampling and randomly divided into control and intervention groups. The neurological tests included missing scan, day and night stroop, continuous performance test and trial making test. In the intervention program, parents were taught how to use effective strategies and skills to manage cognitive deficits in children, based on Tameshk package. Data was analyzed by repeated measure analysis of variance (ANOVA). Results: From the results of data analysis, compensatory rehabilitation had a significant effect on working memory (P<0.00), inhibition (P<0.00, errors; P<0.00, time) and shifting attention (P<0.01 errors in section A; P<0.00, time section A) in children. Conclusion: Compensatory rehabilitation utilizes skills and instructions to improve cognitive functions in children. The current research showed that training by compensation approach could improve neuropsychological functions in children with ADHD.